Let's complete the process step by step:
-
Start with the original equation: \[ 14(-r - 2) - 10r = -4 \]
-
Apply the distributive property: \[ 14 \cdot -r + 14 \cdot -2 - 10r = -4 \] This simplifies to: \[ -14r - 28 - 10r = -4 \]
-
Combine like terms: \[ -14r - 10r - 28 = -4 \] Which simplifies to: \[ -24r - 28 = -4 \]
-
Now add 28 to both sides: \[ -24r - 28 + 28 = -4 + 28 \] Simplifying gives: \[ -24r = 24 \]
-
Next, divide both sides by -24: \[ r = \frac{24}{-24} \] Simplifying this results in: \[ r = -1 \]
Now, filling in the missing terms and descriptions:
-
The first part complete: \[ -28 = -4 \quad \text{(after distributing and simplifying)} \]
-
Missing descriptions:
- Apply the distributive property
- Combine like terms
- Add 28 to both sides
- Divide both sides by -24
Final answer: \[ r = -1 \]